2022
DOI: 10.1111/dth.15933
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab dose spacing after initial successful treatment or adverse events in adult patients with atopic dermatitis: A retrospective analysis

Abstract: Strategies on long‐term management of patients affected by atopic dermatitis (AD) undergoing treatment with dupilumab achieving good clinical response (GCR) or experiencing dupilumab‐related adverse events (AEs) are scant. Data of patients who implemented longer than scheduled dupilumab dosing interval due to GCR (at least 52 weeks of treatment and controlled AD activity [Eczema Area Severity Index ≤7 and Dermatology Life Quality Index ≤5 for at least 6 months]) or AEs (dupilumab‐related and treatment‐resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Patruno et al. found improvement of ocular symptoms in 46.6% ( n = 7/15) of the patients with DAOSD after prolongation of the dosing interval to 300 mg every 3–4 weeks, without worsening of AD 45 . In addition, Spekhorst et al.…”
Section: Part Ii: Dupilumab‐associated Ocular Surface Disease In Atop...mentioning
confidence: 98%
See 1 more Smart Citation
“…Patruno et al. found improvement of ocular symptoms in 46.6% ( n = 7/15) of the patients with DAOSD after prolongation of the dosing interval to 300 mg every 3–4 weeks, without worsening of AD 45 . In addition, Spekhorst et al.…”
Section: Part Ii: Dupilumab‐associated Ocular Surface Disease In Atop...mentioning
confidence: 98%
“…10 Patruno et al found improvement of ocular symptoms in 46.6% (n = 7/15) of the patients with DAOSD after prolongation of the dosing interval to 300 mg every 3-4 weeks, without worsening of AD. 45 In addition, Spekhorst et al reported persistent AD control in patients who tapered the dosage of dupilumab due to controlled AD. 46 The beneficial effect of dose reduction on DAOSD seems in contrast to the study by Akinlade et al, who pooled data on dupilumab concentrations of phase 3 dupilumab trials from baseline to week 16 and suggested that the incidence of DAOSD may decrease with higher serum concentrations of dupilumab.…”
Section: Effect Of Dose Adjustment Of Dupilumab On Daosdmentioning
confidence: 99%
“…Driven by numerous evidences on the possible lengthening of the interval between doses after the clearance of the disease, [7][8][9] we decided to do so with our patients on dupilumab therapy.…”
Section: Lengthening the Time Intervals Between Doses Of Dupilumab In...mentioning
confidence: 99%
“…Recently, the possibility of extending intervals to every 3 (Q3W) or 4 weeks (Q4W) has been discussed, with clinical and pharmaco-economic benefits. [1][2][3][4] We conducted a prospective observational study at an AD referral centre to evaluate the persistence rate of tapering dupilumab. Patients with moderate-to-severe AD treated with Q2W dupilumab were tapered to Q3W or Q4W based on clinical decision.…”
mentioning
confidence: 99%
“…5 Tapering can also be performed to manage refractory adverse effects such as PFE or conjunctivitis. 1,4 Paradoxical facial erythema is probably related to the immunological shift from a dupilumab's T2-blocked response to a (now) unchecked T1/T17 pathways, which in turn would amplify a T17-response against Malassezia or unmask a T1/T17mediated allergic contact dermatitis. 6,7 We found that resuming on-label dupilumab dosing due to AD worsening with tapering led to a complete reacquisition of response, providing clinicians with encouraging data to try this approach in selected patients.…”
mentioning
confidence: 99%